2019
DOI: 10.3389/fnhum.2019.00028
|View full text |Cite
|
Sign up to set email alerts
|

A Non-cognitive Behavioral Model for Interpreting Functional Neuroimaging Studies

Abstract: The dominant model for interpreting brain imaging experiments, which we refer to as the Standard Cognitive Model (SCM), assumes that the brain is organized in support of mental processes that control behavior. However, functional neuroimaging experiments of cognitive tasks have not shown clear anatomic segregation between mental processes originally proposed by this model. This failing has been blamed on limitations in imaging technology and non-linearity in the brain’s implementation of these processes. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 97 publications
(196 reference statements)
1
1
0
Order By: Relevance
“…Although evidence for nonlinear, main effect relationships was limited, we found that nonlinear POPs–work outcomes relationships surfaced when higher worker loyalty was reported. These results add support for reexamining the prevailing perspective inherent in linear views across disciplines (Belzak & Bauer, 2019; Shulman & Rothman, 2019). However, the relationships between POPs and satisfaction approximated a more linear association for less loyal employees.…”
Section: Discussionsupporting
confidence: 63%
“…Although evidence for nonlinear, main effect relationships was limited, we found that nonlinear POPs–work outcomes relationships surfaced when higher worker loyalty was reported. These results add support for reexamining the prevailing perspective inherent in linear views across disciplines (Belzak & Bauer, 2019; Shulman & Rothman, 2019). However, the relationships between POPs and satisfaction approximated a more linear association for less loyal employees.…”
Section: Discussionsupporting
confidence: 63%
“…Individuals engage more strongly in what they do if they feel right about it and if it fits with their decisions and prior engagement. Their engagement may include the enjoyment of performing the behavior as such or the enjoyment of immediate outcomes of the behavior (Hall & Fong, 2007;Shulman & Rothman, 2019). After the initial adoption of new behaviors, individuals are theorized to evaluate the results of their efforts cognitively and emotionally.…”
Section: Perceived Enjoymentmentioning
confidence: 99%